Selection of Scholarship Students in Higher Education with VIKOR Method - Kubra Akıllı; Emre İpekçi Çetin (International Journal of Assessment Tools in Education)
Selection of students who will benefit from scholarships given in the university are usually done by formed commission. Due to limited number of scholarships offered, commission are obliged to choose the most appropriate students. In this selection process, it is important to make objective evaluation. The commission should mostly interview the applicants face to face. This situation causes time and labour loss and a stressful environment for both members of the commission and the students. An objective scoring system could solve the problems discussed above. In this study, 200 students who applied for the scholarship at Akdeniz University Faculty of Economics and Administrative Sciences to the scholarship were ranked. In this study, firstly the selection criteria of students for the scholarship was determined with the help of researchers and social aid service experts. Then, the weights of the criteria were calculated by the SWING method. These weights were used to rank the students who were eligible for the scholarship by using the VIKOR method. This method will make an objective evaluation and will accelerate the selection process.